A review of national shoulder and elbow joint replacement registries. - Rasmussen, J; Olsen, B; Fevang, B; Furnes, O; Skytta, E; Rahme, H; Salomonsson, B; Mohammed, K; Page, R; Carr, A (2012)
The aim was to review the funding, organization, data handling, outcome measurements, and findings from existing national shoulder and elbow joint replacement registries; to consider the possibility of pooling data between registries; and to consider wether a pan european registry might be feasible.